Genetic Analysis of Amino Acid Accumulation in opaque-2 Maize Endosperm - Wang, Xuelu (American Society of Plant Physiologists, 2001)
The opaque-2 mutation in maize (Zea mays) is associated with an increased level of free amino acids (FAA) in the mature endosperm. In particular, there is a high concentration of lysine, the most limiting essential amino acid. To investigate the basis for the high-FAA phenotype of opaque-2 maize, we characterized amino acid accumulation during endosperm development of several wild-type and opaque-2 inbreds. Oh545o2 was found to have an exceptionally high level of FAA, in particular those derived from aspartate (Asp) and intermediates of glycolysis. The FAA content in Oh545o2 is 12 times greater than its wild-type counterpart, and three and 10 times greater than in Oh51Ao2 and W64Ao2, respectively. We crossed Oh545o2 to Oh51Ao2 and analyzed the F(2:3) progeny to identify genetic loci linked with the high FAA level in these mutants. Quantitative trait locus mapping identified four significant loci that account for about 46% of the phenotypic variance. One locus on the long arm of chromosome 2 is coincident with genes encoding a monofunctional Asp kinase 2 and a bifunctional Asp kinase-homo-Ser dehydrogenase-2, whereas another locus on the short arm of chromosome 3 is linked with a cytosolic triose phosphate isomerase 4. The results suggest an alternation of amino acid and carbon metabolism leads to overproduction and accumulation of FAA in opaque-2 mutants.